Organized crime - Lampe, Klaus von, 1961- (Los Angeles, CA : SAGE Publications, Inc, 2016)
Organized Crime: Analyzing Illegal Activities, Criminal Structures, and Extra-legal Governance provides a systematic overview of the processes and structures commonly labeled'organized crime,' drawing on the pertinent empirical and theoretical literature primarily from North America, Europe, and Australia. The main emphasis is placed on a comprehensive classificatory scheme that highlights underlying patterns and dynamics, rather than particular historical manifestations of organized crime. Esteemed author Klaus von Lampe strategically breaks the book down into three key dimensions: (1) illegal activities, (2) patterns of interpersonal relations that are directly or indirectly supporting these illegal activities, and (3) overarching illegal power structures that regulate and control these illegal activities and also extend their influence into the legal spheres of society. Within this framework, numerous case studies and topical issues from a variety of countries illustrate meaningful application of the conceptual and theoretical discussion.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Organized crime